Preparing Teachers to Re-Build Democratic Communities and Disappearing Middle Class to Reverse Global Inequality: A Typology Applying Bourdieusian 'Taste' and Dewey-Inspired Tools to Transform World Making - Alison Taysum; Soheil Salha (MDPI AG, 2024)
'Double structuring' of objective economic wealth and subjective perception of wealth through language and culture produce a common world of divisions in the classroom from 'bad taste' to 'good taste'. Teachers' language and culture of instruction and 'good taste' perpetuate systemic injustice with unconscious bias. The tool 'A Blueprint for Character Development for Evolution (ABCDE) offers five steps to prepare teachers to recognize bias and reverse it with a Typology Applying Bourdieusian 'Taste' for Making Worlds. A-Ask questions about instructional Language and Culture and Community Languages and Cultures; B-Critique Typology of Taste: C-Develop statistical models with measures to monitor and evaluate incremental progress towards synthesizing/unifying different classroom languages and cultures into one democratic language and culture whilst honouring each; D-Create evidence-informed, logical and ethical qualitative pathways to re-building a democratic community/disappearing middle class; E-Identify a principle of unity that reverses local inequality, and through powerful Higher Education networks, mainstream it to reverse global inequality. A Professional Educators and Administrators Committee for Empowerment (PEACE) offers a systemic multi-level communication infrastructure to enable feedback loops from communities to policy makers to measure inequality and report narrowing income and wealth gaps to reverse the sharpest increase between 2019 and 2020 in global inequality since World War II.